The degree of inclusion of linguistic intelligence standards in Arabic language textbooks for the seventh and eighth grades in Syria (Damascus University Journal of educational and Psychologyical sciences, 2024)
The study aims to identify to what extant is  the linguistic intelligence standards and indicators in educational and instructional activities available in Arabic books for the seventh and eighth grades of the second cycle of basic education in Syria. To achieve the purpose of this study, the researcher prepared the checklist for analyzing  the Linguistic Intelligence Standards and Indicators, and then the instructional and evaluative activities are analyzed according to  the steps of analysis and the methodology of content, taking into account the rules of analysis.The study aims to determine the linguistic intelligence standards and indicators that are now available in Arabic books for the seventh and eighth grades of Syria's second cycle of basic education. To achieve the study's goal, the researcher formed a checklist for analysing the Linguistic Intelligence standards and indicators, and then the instructional and evaluative activities were analysed using the steps of analysis and content methodology, while keeping the rules of analysis in mind.The results of the study reveal that:- The educational and evaluative activities focused on the criterion: "Content promotes language outcomes and helps to employ them" to a high degree . Most standards of linguistic intelligence have been met in Arabic book activities for the seventh and eighth grades to varying degrees.- Most linguistic intelligence standards have been attained to varied degrees in Arabic book activities for the seventh and eighth grades.- The Arabic language books have met the majority of the linguistic intelligence standards and indicators, but they do not provide a clear picture of the level of processing of each of their indicators, indicating that there are no relative weights for each indicator of linguistic intelligence standards.
Keywords: Linguistic Intelligence; Instructional And Evaluative Activities; Arabic Language Books